2019
DOI: 10.1002/sdtp.12925
|View full text |Cite
|
Sign up to set email alerts
|

25‐1: Invited Paper: Achieving high uniformity and yield of 200 mm GaN‐on‐Si LED epiwafers for micro LED applications with precise strain‐engineering

Abstract: One of the big challenges of micro LED displays is to reduce cost/increase yield and establish excellent manufacturability. Galliumnitride on silicon (GaN-on-Si) LED epiwafers offer fundamental cost advantages to the entire process flow for micro LEDs compared with conventional GaN-on-sapphire LED epiwafers. However, due to the difficulties of epitaxial growth of GaN-on-Si, demonstration of such cost advantages in micro LED application is not wide-spread yet. In this presentation, we have demonstrated excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…198 In 2019, Nishikawa et al reported a precise strain-engineering method using Veeco's Propel to achieve high uniformity and yield in μLEDs. 199 Mass Transfer. The most crucial technical challenge associated with μLED fabrication is mass transfer.…”
Section: ■ Emerging Applications Of μLedsmentioning
confidence: 99%
See 1 more Smart Citation
“…198 In 2019, Nishikawa et al reported a precise strain-engineering method using Veeco's Propel to achieve high uniformity and yield in μLEDs. 199 Mass Transfer. The most crucial technical challenge associated with μLED fabrication is mass transfer.…”
Section: ■ Emerging Applications Of μLedsmentioning
confidence: 99%
“…Several types of mass transfer techniques are currently being researched and developed to improve the efficiency and yield to reduce the cost of μLEDs, such as electrostatic stamping, fluid transfer, elastomer stamping, etc. 199 At present, the RGB three-color monochromatic chip and mass transfer technology are immature, and it is very important to develop other technologies to realize full-color μLEDs. The transfer process of monochromatic μLEDs is much simpler than that of RGB μLED counterparts, and the realization of full-color μLED displays can also utilize color-conversion methods, which can effectively reduce manufacturing costs, especially in the mass transfer, correlation detection, and compensation drive parts of the circuit through transfer.…”
Section: ■ Emerging Applications Of μLedsmentioning
confidence: 99%
“…LED epitaxy on silicon wafers brings some unique challenges but also offer more opportunities for wafer strain engineering [2] . However, Silicon is not the only option for large diameter.…”
Section: Figure 3: Economics Drive the Die Size For Microled Display Applicationsmentioning
confidence: 99%
“…While this approach represents the optimal path for the manufacturing of stand-alone components to be included in discrete-based systems, it severely limits the direct inclusion of optical emitters into Si-based electronic and photonic circuits [2], which would allow fabricating low-cost fully integrated electrophotonic circuits for a variety of silicon photonics applications. In fact, while efficient and reliable III-N visible LEDs can be grown on silicon substrates despite the presence of lattice mismatch-related extended defects [3][4][5], continuous-wave (CW) laser operation of IR semiconductor devices requires very-low defect densities to be present within the active region of the devices. Several strategies have been studied and implemented to achieve epitaxial integration of III-V materials on silicon [6][7][8], but none of these ensured high enough efficiency and scalability to promote their adoption for large-scale integration into Si-and SOI-based photonic and electronic circuits.…”
Section: Introductionmentioning
confidence: 99%